2016
DOI: 10.1007/s00432-016-2262-9
|View full text |Cite
|
Sign up to set email alerts
|

Management of prostate cancer patients with locally adverse pathologic features after radical prostatectomy: feasibility of active surveillance for cases with Gleason grade 3 + 4 = 7

Abstract: For the appropriate patient, depending on age, physical condition, early postoperative PSA, patient desire, etc., could be a candidate for wait and see policy with specimen GGG 2 disease, so to distinguish this from GGG 3 may facilitate discussions at the point of treatment decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, validation of the GG system with larger and different regional cohorts as well as long-term clinical outcome is still warranted. A recent report demonstrated that the GG system correlates well with prostate cancer specific death,27 but this study used cases diagnosed as far back as 1990 28. Another recent study with almost 10 000 patients from 2005 to 2014 claimed that the GG system is clinically negligible in terms of biochemical recurrence and clinical local and/or nodal recurrence 29.…”
Section: Discussionmentioning
confidence: 98%
“…However, validation of the GG system with larger and different regional cohorts as well as long-term clinical outcome is still warranted. A recent report demonstrated that the GG system correlates well with prostate cancer specific death,27 but this study used cases diagnosed as far back as 1990 28. Another recent study with almost 10 000 patients from 2005 to 2014 claimed that the GG system is clinically negligible in terms of biochemical recurrence and clinical local and/or nodal recurrence 29.…”
Section: Discussionmentioning
confidence: 98%
“…With the increased public awareness and wide use of PSA-based screening, the number of patients diagnosed with PCa annually has been increasing [ 6 ]. Because RP provides superior cancer control and functional outcomes, this surgery has become a standard first-line treatment for eligible patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…of patients Recruitment period Age (years) p-PSA (ng/ml) Follow-up (months) Surgical approach Wettstein et al [ 35 ] 2017 Switzerland 371 2008–2015 Median (range) 63 (41–78) Median (range) 6.79 (0.43–81.4) Median (range) 28 (1–64) NA Xun et al [ 6 ] 2017 China 172 2003–2014 Median (IQR) 68 (62–72) Median (IQR) 16.1 (10.9–28.3) Median (IQR) 46.4 (33.4–62.4) NA Meyer et al [ 36 ] 2017 Germany 903 1992–2005 Median (IQR) 63 (59–66) Median (IQR) 6.4 (4.6–9.0) Median (IQR) 133 (97–157) NA Gandaglia et al [ 37 ] 2017 Multi-centred 94 2011–2015 Median (IQR) 64.3 (57.1–68.9) Median (IQR) 9.7 (5.1–17.5) Median (IQR) 23.5 (18.7–27.3) Robot-assisted RP Shangguan et al [ 33 ] 2016 China 172 2003–2014 Median (range) 68 (62–72) Median (range) 16.1 (10.9–28.3) Median (IQR) 46.4 (33.4–62.4) Open and laparoscopic RP Zhang et al [ 34 ] 2016 China 168 2006–2011 Median (range) 69 (53–85) Median (range) 13.31 (4.59–36.12) Median (range) 68 (7–98) Laparoscopic RP Simon et al [ 12 ] 2016 Multi-centres 411 2001–2013 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BCR after RP is often assumed to represent clinical progression or distant metastases, indicating that the patients will need to be treated with secondary treatment. [4,5]…”
Section: Introductionmentioning
confidence: 99%